1994
DOI: 10.5547/issn0195-6574-ej-vol15-no4-2
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Responses to Oil Price Increases and Decreases in Seven OECD Countries

Abstract: The correlations between oil-price movements and GDPjluctuations are investigatedfor the United States, Canada, Japan, Germany (West), France, the United Kingdom, and Norway. The responses to price increases and decreases are allowed to be asymmetric. Bivariate con-elations as well as partial wrrelations within a reduced-form macroeconomic model are considered. We correlations with oil-price increases are negative and signijcant for most countries, but positive for Norway, whose oil-producing sector is large r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(70 citation statements)
references
References 14 publications
10
53
0
1
Order By: Relevance
“…Some authors have argued that this breakdown of the relationship reveals that the relationship between the variables is non-linear, and thus have proposed different specifications of it, particularly asymmetric ones. These specifications can be implemented either by introducing two separate variables for oil price increases and decreases, as in the models suggested by Mork (1989) and Mork et al (1994), or by estimating Markov regime-switching models characterized by high and low inflation periods (Çatik and Önder, 2011), or even by using a quantile regression framework to estimate the marginal effect on inflation in the distribution (Chortareas et al, 2012). Other authors have suggested different ways to take time variation into account, either by splitting the sample into two sub-periods assuming a structural break in the early 1980s, by estimating regressions over rolling time windows, or by using time-varying parameters models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors have argued that this breakdown of the relationship reveals that the relationship between the variables is non-linear, and thus have proposed different specifications of it, particularly asymmetric ones. These specifications can be implemented either by introducing two separate variables for oil price increases and decreases, as in the models suggested by Mork (1989) and Mork et al (1994), or by estimating Markov regime-switching models characterized by high and low inflation periods (Çatik and Önder, 2011), or even by using a quantile regression framework to estimate the marginal effect on inflation in the distribution (Chortareas et al, 2012). Other authors have suggested different ways to take time variation into account, either by splitting the sample into two sub-periods assuming a structural break in the early 1980s, by estimating regressions over rolling time windows, or by using time-varying parameters models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, since Mork [40] finds that an increase in the price of oil has a greater influence on a country’s macroeconomy than a decrease, the asymmetric effects of oil prices have grabbed the attention of researchers [4146]. Mork et al [47] conclude that an increase in the oil price has a negative effect on GDP, whereas a decrease in the oil price has not been found to have a positive impact on output or an impact to the same degree. Hu et al [48] analyze the short-run and long-run asymmetric impact of oil price shocks on China’s stock market and find that the demand-side shocks have a significant impact in both the short and long run and that only the aggregate demand shock has an asymmetric effect.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Mork (1989) decided to test the influence of declines and increases in oil price on the economic growth, he showed that the coefficient on oil price increases are highly significant and negative. In another work, Mork et al (1994) showed that for the most of European countries a negative relationship between oil price increases and GDP growth occurs. However, evidence for the causal relationship between oil prices and economic growth was not always confirmed in empirical studies.…”
Section: A Brief Overview Of the Empirical Studiesmentioning
confidence: 98%